Harnessing database-supported high-throughput screening for the design of stable interlayers in halide-based all-solid-state batteries - Longyun Shen; Zilong Wang; Shengjun Xu; Ho Mei Law; Yanguang Zhou; Francesco Ciucci (Nature Communications)
Abstract All-solid-state Li metal batteries (ASSLMBs) promise superior safety and energy density compared to conventional Li-ion batteries. However, their widespread adoption is hindered by detrimental interfacial reactions between solid-state electrolytes (SSEs) and the Li negative electrode, compromising long-term cycling stability. The challenges in directly observing these interfaces impede a comprehensive understanding of reaction mechanisms, necessitating first-principle simulations for designing novel interlayer materials. To overcome these limitations, we develop a database-supported high-throughput screening (DSHTS) framework for identifying stable interlayer materials compatible with both Li and SSEs. Using Li3InCl6 as a model SSE, we identify Li3OCl as a potential interlayer material. Experimental validation demonstrates significantly improved electrochemical performance in both symmetric- and full-cell configurations. A Li|Li3OCl|Li3InCl6|LiCoO2 cell exhibits an initial discharge capacity of 154.4 mAh/g (1.09 mA/cm2, 2.5–4.2 V vs. Li/Li+, 303 K) with 76.36% capacity retention after 1000 cycles. Notably, a cell with a conventional In-Li6PS5Cl interlayer delivers only 132.4 mAh/g and fails after 760 cycles. An additional interlayer-containing battery with Li(Ni0.8Co0.1Mn0.1)O2 as the positive electrode achieves an initial discharge capacity of 151.3 mAh/g (3.84 mA/cm2, 2.5–4.2 V vs. Li/Li+, 303 K), maintaining stable operation over 1650 cycles. The results demonstrate the promise of the DSHTS framework for identifying interlayer materials.